2017
DOI: 10.1016/j.cej.2016.11.073
|View full text |Cite
|
Sign up to set email alerts
|

New insights in the metabolic behaviour of PAO under negligible poly-P reserves

Abstract: In a previous study the authors confirmed the ability of PAOs to perform GAO metabolism in short-term experiments. However, what happens when PAOs are exposed to poly-P shortage for an extended period of time? The answer to this question was the aim of this work from a macroscopic and microscopic point of view. Therefore, the poly-P was removed from a PAO enriched SBR and maintained without poly-P during five solid retention time. The PAOs were found to quickly change their metabolism to a clear GAO performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…were originally isolated as aromatic compound-degrading bacteria and facultative anaerobic nitrate-reducing bacteria [16,17]. Since then, several Dechloromonas populations have been shown to accumulate poly-P and PHA in situ and/or in axenic cultures [11,13], and several studies have also suggested their potential role as PAOs [18][19][20]. Furthermore, analysis of the Dechloromonas aromatica strain RCB genome revealed the genes required for poly-P accumulation, including polyphosphate kinase, and exopolyphosphatase [21].…”
Section: Introductionmentioning
confidence: 99%
“…were originally isolated as aromatic compound-degrading bacteria and facultative anaerobic nitrate-reducing bacteria [16,17]. Since then, several Dechloromonas populations have been shown to accumulate poly-P and PHA in situ and/or in axenic cultures [11,13], and several studies have also suggested their potential role as PAOs [18][19][20]. Furthermore, analysis of the Dechloromonas aromatica strain RCB genome revealed the genes required for poly-P accumulation, including polyphosphate kinase, and exopolyphosphatase [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, our results revealed that the fraction of PAOs that contain PHV could vary as well with different operational loading conditions, irrelevant to the abundance of GAOs. Acevado et al (2012, 2017) showed that long-time P limited conditions enhance glycolytic pathway to supply energy deficit and shift towards more GAO-like metabolism. It was observed later by da Silva et al (2018) that when polyP is limited, reverse (split) TCA cycle is the most optimal pathway suggesting GAOs are operating reverse TCA cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Although the input space was sampled to conform to the assumptions of the metabolic model, i.e., within a narrow range of temperatures, pH and an influent mixture of HAc and HPr, the predictions may not be valid in situations where the PAO population is subject to limiting conditions for extended periods of time. For instance, PAO have been found to shift from PHA to glycogen accumulation in anaerobic conditions following a lack of PO 4 in the influent (Acevedo et al, 2014, 2017)—a phenotypic behavior characteristic of their GAO competitors. Similarly, PAO have been shown to employ the tricarboxylic acid (TCA) cycle to supplement the production of reducing agents to cope with a lack of VFA in the influent, or due to glycogen depletion, possibly as a result of prolonged periods of cellular maintenance (Lanham et al, 2013, 2014).…”
Section: Discussionmentioning
confidence: 99%